PEMAKAIAN MAJAS DI ANTOLOGI PUISI PADA CIPTAAN SAPARDI DJOKO DAMONO - Fajar Alamsyah (Scolae: Journal of Pedagogy, 2020)
The problem discussed in this study regarding the style of language used by Sapardi Djoko Damono in his work isPaper Boat Poetry Collection. This paper intends to describe the use of the art used by Sapardi Djoko Damono in theAnthology of Paper Boat Poetry. This paper uses a descriptive method, which describes the composition contained inthe anthology of Paper Boat Poetry created by Sapardi Djoko Damono. This study uses Miles Huberman analysis (datareduction, data presentation, and conclusion drawing). Based on the analysis results, it can be concluded that in PaperBoat Poetry Anthology created by Sapardi Djoko Damono found various majas, including a) rhetorical style whichincludes alliteration, Asonance, Asindeton, Polisindeton, Histeron Proteron, Pleonasme, Prolepsis or Anticipation, andHyperbolic. Then, b) figure of speech which includes the style of Equality or Simile, Metaphor, Personification,Metonimia, Antonomasia, and Hypalase. The majority of majas that are used in the Paper Boat Poetry Anthologycreated by Sapardi Djoko Damono are alliteration majors.